The Impact of Fintech on Financial Inclusion in Emerging Economy of Major Cities in Indonesia - Ernawaty, Lisa; Mujanah, Siti; Fianto, Achmad Yanu Alif (Rekayasa, 2025)
This study investigates the impact of financial technology (FinTech) adoption on financial inclusion in emerging economies using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through a survey of 450 respondents from three emerging city (Surabaya, Makassar, and Medan) to measure the relationships among FinTech accessibility, financial literacy, trust in digital platforms, and financial inclusion. The measurement model showed good reliability and validity, with Cronbach’s Alpha ranging from 0.84 to 0.90 and Average Variance Extracted (AVE) above 0.60. Structural model results indicated that FinTech accessibility (β = 0.35, p 0.01) and financial literacy (β = 0.29, p 0.01) have significant positive effects on financial inclusion. Trust in FinTech platforms also contributed positively (β = 0.21, p 0.05) and acted as a mediator between FinTech accessibility and financial inclusion (indirect β = 0.11, p 0.05). The model explained 62% of the variance in financial inclusion (R² = 0.62), suggesting strong explanatory power. These findings confirm that FinTech innovations not only improve access to financial services but also enhance their effective use when combined with higher trust and literacy levels. The study contributes to the digital finance literature and provides practical recommendations for policymakers to promote inclusive growth.